A study of Effects and implications of differences between Indian GAAP and IFRS - Srivastava, Anubha (KnE Social Sciences, 2020)
Economic growth in any economy requires sustainable high-quality financial reporting standards. However in the era of globalization, with rapidly changing rules and regulations in accounting world, Indian financial reporting system too cannot be isolated from the global developments. Lack of standardization in different accounting standards imposes a financial burden on all the stakeholders, which includes both internal as well as external burden to an organization. It is also too cumbersome for investors to compare the financial statement of corporates if they follow different accounting policy. It was felt that there should be one global set of accounting standards for all. Thus IASB came in existence and formulated IFRS. IFRS is high-quality principle-based accounting standard which aims to bring uniformity comparability and transparency in accounting world. In India the conversion process has started in 2015-16 onwards where all the accounting standards will be gradually fully converged with IFRS and will be named as Ind as. This paper attempts to find out the key difference among IFRS, Indian GAAP and ind AS and its implications. A questionnaire survey has been conducted to find out the implication of differences. The paper concludes that adoption of IFRS would benefit the economy in all aspects. Keywords: IFRS, Indian GAAP, Ind AS, key difference between IFRS, Ind AS and Indian GAAP, IFRS adoption,